Did the Buddha Teach to Be Called ‘Buddha’?―Focusing on the Meaning of Brāhmaṇa and How Buddhist Authors (re)Formulated His Words to Praise Him― - Efraín Villamor Herrero (Religions)
The attainment of enlightenment by Gautama Buddha is the very beginning of Buddhism as a religious phenomenon. Because of his attainment of enlightenment, he has been remembered as Buddha for centuries, even though it is uncertain whether buddha was the preferred title to remember him by from the earliest times. Previous scholarship has demonstrated that the term buddha was a common noun in the Indian religious context, and it was also employed to refer to his higher disciples. The verses of the Suttanipāta represent a complex corpus rich in many fundamental concepts common to Jain religious thought. Many epithets were introduced by Buddhists to praise their monastic founder as Jains do. Among them, buddha does not seem to be the preferred one among them. Contrarily, by redefining brāhmaṇa, Buddhists participate in the ascetic discourse of praising their master as the one who deserves to be regarded as that ideal. This paper argues that Buddhists advocated their master as a brāhmaṇa, a title that is not only consistent with the teachings of Jains but also one that may have preceded the popularity of Buddha as his most memorable title.